VALUASI PREMI SYARIAH MENGGUNAKAN DEFLATOR DENGAN PENDEKATAN MODEL HULL-WHITE - , RISMA ARYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the principles in Islamic economics is the in existence concept of time value of money and prohibition of usury (riba) in any forms. This principle does not remove random factor in profit-earning orloss of a business. The observation of random factor treatment is done at equivalent rate fluctuation movement. Fluctuation of equivalent rate is taken from historical data of previous periodic of a dinar institution. To show the movement of equivalent rate fluctuation, Hull-White model approach is utilized as previously estimation process is done towards the parameters. Furthermore, the equivalent rate fluctuation and equivalent rate value estimation of the next periodic is illustrated using Ordinary Least Square Regresion. Discretization of Hull-White Model equation is introduced as deflator which is used as Islamic discounting factor.